PERAN PENDIDIKAN DALAM PROSES PEMBELAJARAN INKLUSIF (STUDI KASUS DI SD MUHAMMADIYAH DADAPAN KABUPATEN SLEMAN) - Arum Umamil Banati; Nurul Hidayati Rofiah (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
Inclusive learning is to provide a service system for children with special needs to be served in the nearest school or regular school with their peers. In the implementation of inclusive learning in schools requires serious handling from related parties, especially parents, the school, government and the community. Therefore, researchers want to know how the role of educators in the inclusive learning process in SD Muhammadiyah Dadapan Sleman District. This research is a qualitative research with descriptive approach of case study. The subject of this research is principal, classroom teacher, subject teacher, special tutor and student. Target object in this research is the role of educator (classroom teacher, special tutor, and children with special needs) in inclusive learning at SD Muhammadiyah Dadapan, Sleman District.Based on the research results obtained conclusions as follows: (1) Educators referred to in this study are classroom teachers, special tutors and subject teachers. The role of special mentor teachers is only as a consultant if the class teacher has difficulty in guiding students with special needs during the learning process in the classroom. The role of classroom teachers and subject teachers is crucial in the inclusive learning process, in schools because students with special needs are more often guided by classroom teachers and subject teachers. (2) Competent educators will be better able to create an effective, enjoyable learning environment, and will be better able to manage the class, so that learning can run optimally. To create a conducive learning atmosphere the educator must have 4 competencies, namely pedagogic competence, personality competence, social competence, and professionalism.